2018
DOI: 10.1111/acem.13655
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach to Predicting Need for Hospitalization for Pediatric Asthma Exacerbation at the Time of Emergency Department Triage

Abstract: Objectives: Pediatric asthma is a leading cause of emergency department (ED) utilization and hospitalization.Earlier identification of need for hospital-level care could triage patients more efficiently to high-or low-resource ED tracks. Existing tools to predict disposition for pediatric asthma use only clinical data, perform best several hours into the ED stay, and are static or score-based. Machine learning offers a population-specific, dynamic option that allows real-time integration of available nonclinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 33 publications
(49 reference statements)
0
71
0
Order By: Relevance
“…For example, supervised ML interventions included prediction models for pediatric asthma exacerbation, prediction of return visits, and stroke diagnosis. [19][20][21] NLP models were used to optimize resource allocation in low-resource settings, classify computed tomography (CT) imaging, and predict hospital admission using electronic medical records (EMR). [22][23][24] There also appears to be rapidly growing interest in the varied opportunities for AI, as most studies were published in the last 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, supervised ML interventions included prediction models for pediatric asthma exacerbation, prediction of return visits, and stroke diagnosis. [19][20][21] NLP models were used to optimize resource allocation in low-resource settings, classify computed tomography (CT) imaging, and predict hospital admission using electronic medical records (EMR). [22][23][24] There also appears to be rapidly growing interest in the varied opportunities for AI, as most studies were published in the last 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we found that AI interventions in the ED are heterogeneous in both purpose and design. For example, supervised ML interventions included prediction models for pediatric asthma exacerbation, prediction of return visits, and stroke diagnosis 19–21 . NLP models were used to optimize resource allocation in low‐resource settings, classify computed tomography (CT) imaging, and predict hospital admission using electronic medical records (EMR) 22–24 .…”
Section: Discussionmentioning
confidence: 99%
“…In a real-world validation study, the HAI system improved the accuracy of hip fracture diagnosis to 97%, with a false-negative rate of 0.65%. Several reports have shown that the algorithm might help physicians in acute care and could save lives [10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the possibility of using algorithms trained with a large amount of data to aid in appropriate triage, accurately predicting outcomes, improving diagnoses and referrals in clinical situations, and even shortening the waiting time for reports [10][11][12][13][14][15]. An increasing amount of supporting evidence shows that the use of computer vision with deep neural networks-a rapidly advancing technology ideally suited to solving image-based problems-achieves excellent performance, comparable to that of experts [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Consider education or electronic decision support as interventions for a quality improvement project to reduce disparities in care. Use machine learning to analyze large data sets (eg, all ED visits, [ 19 ] asthma registry) to identify associations between risk factors and poor asthma outcomes previously not considered. Collaborate with local resources to mitigate risk (legal aid to assist with poor housing, care coordination to ensure medications prescribed are covered and there is subspecialty follow-up).…”
Section: Epidemiology and Prevalencementioning
confidence: 99%